2006
DOI: 10.1158/1078-0432.ccr-05-1581
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase 2 Expression in Colorectal Cancer with DNA Mismatch Repair Deficiency

Abstract: Background: Cyclooxygenase 2 (COX-2) overexpression is a frequent but not universal event in colorectal cancer. It has been suggested that COX-2 protein expression is reduced in colorectal cancer with a defective mismatch repair (MMR) system, a phenomenon commonly associated with hereditary nonpolyposis colorectal cancer (HNPCC) but also present in up to15% of sporadic tumors. Aim:To assess COX-2 expression in a large series of fully characterized colorectal cancer patients with respect to the MMR system and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 35 publications
3
22
0
2
Order By: Relevance
“…At the same time, P53-positive rates were rare in serrated polyps. P53 overexpression appears to become more frequent as tumors progress to higher grades of neoplasia, in agreement with previous studies (36,37).…”
Section: ------------------------------------------------------------supporting
confidence: 92%
“…At the same time, P53-positive rates were rare in serrated polyps. P53 overexpression appears to become more frequent as tumors progress to higher grades of neoplasia, in agreement with previous studies (36,37).…”
Section: ------------------------------------------------------------supporting
confidence: 92%
“…In a recent study [56], it was confirmed that while most MMR-proficient CRC exhibited COX-2 overexpression, half of those tumors with a deficient repair system did not overexpress this protein. Interestingly, the lack of COX-2 overexpression was observed almost exclusively in patients with MMR-deficient sporadic forms, thus suggesting an epigenetic mechanism responsible for gene silencing.…”
Section: Selective and Non-selective Cox-2 Inhibi-tors In Lynch Syndromementioning
confidence: 88%
“…It is believed that the mechanism of suppression is related to inhibi on of cyclooxygenase-2 (COX2), as it has been found to be overexpressed in many cancers (colorectal cancer, including HNPCC; bladder cancer; oesophageal cancer, and others) [553][554][555]. The prolonged use of specific COX-2 inhibitors has been found to be associated with decreased risk for colorectal cancer [556,557]; but, somewhat paradoxically, with increased risk for breast cancer and haematological cancers [558].…”
Section: Re Noblastomamentioning
confidence: 99%